On Kronecker Product Of Two RL-graphs And Some Related Results - Elham Raisi Sarbizhan; Mohammad Mehdi Zahedi (Journal of Mahani Mathematical Research)
Using the kronecker product definition of two simple graphs, the kronecker product of two RL-graphs was defined and is defined and it is further shown to be an RL-graph. Ultimately, in light of the  above, some related theorems are proved and several examples are provided to illustrate these new notions.